2000
DOI: 10.1097/00004872-200018080-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the renin–angiotensin gene polymorphisms with relation to hypertension in the Japanese

Abstract: Despite a relatively large number of subjects, we did not find significant evidence for disease association in the Japanese population. Given confounding factors in the case-control strategy, the lack of association does not exclude the relevance of the R-A genes to hypertension. Further investigation needs to be performed in large-scale populations, where the use of not only hypertension status, but also 'intermediate' phenotypes would be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
2
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 35 publications
6
36
2
3
Order By: Relevance
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Allele and genotype frequencies were analyzed using the genecounting method, and the Hardy-Weinberg equilibrium, checked by the w 2 -test, was considered to be maintained as described previously. 13,17 First, statistical significance was determined by one-way ANOVA (analysis of variance) or by the w 2 -test. In the case of statistically significant relations, the Bonferroni analysis was applied to assess the relationship between categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kato et al 18 have performed a case-control study in which they failed to find any relation between the gene polymorphisms of the renin-angiotensin-aldosterone system and EH. In the subanalysis of their study, similar criteria to our study were applied to select the normotensive and hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, the overall results are inconsistent. [9][10][11][12][13][14] Most of these studies used a very small limited number of single-nucleotide polymorphisms (SNPs) in the AGT gene (i.e., 1 or 2). The main drawback to this approach is that, if these SNPs are not causal SNPs or are not in strong linkage disequilibrium (LD) with causal SNPs, the power to detect association will be limited.…”
Section: Introductionmentioning
confidence: 99%